The off-Record Politeness Strategy and Cultural Values of the Belis Negotiation Speech Event: A Sociopragmatic Study - Gabriel Fredi Daar; Ni Luh Sutjiati Beratha; I Made Suastra; Ni Wayan Sukarini (Universitas Pendidikan Indonesia, 2023)
This study aims to find out the language politeness strategies applied by the tongka (spokesperson) and other parties involved in the belis negotiation speech event in the Manggarai community, the Pasat-Ruis dialect, Indonesia. This study used a phenomenological approach. Data were collected through in-depth interviews with five key informants with experience as spokespersons (tongka) and adequate knowledge of the Manggarai language and culture. Data were analyzed using the interactive model proposed by Miles and Haberman (1992). The study found that the off-record politeness strategy was applied in two patterns; (1) The use of metaphorical phrases to refine the speech. Knowledge and the ability to interpret the meaning of speech through metaphorical phrases is an important aspect that must be possessed by a tongka (spokesperson) by connecting the phrase with the context of its use so that it can be understood and fulfills the elements of Politeness. (2) The use of sopi while conveying speech. The patterns show Politeness and the distinctive and authentic characteristics of Manggarai culture. Meanwhile, the cultural values of the utterances of belis negotiations include kinship, brotherhood, responsibility, appreciation, and respect. Thus, the findings indicate that the spokespersons selected in the belis negotiation process need to consider the knowledge of Manggarai culture and the ability to use metaphorical phrases in cultural speech so that the belisnegotiation process runs smoothly according to the expectations of the two extended families.